Pieta: the image representation of care - Fernando Porto; Mercedes Neto; Sandra Goulart (Cultura de los Cuidados, 2014)
Reflection on the experience of care over time by the notions of care and time of the philosopher Paul Ricoeur. To this end, we used the image representation of Michelangelo’s Pietá (1498), which resulted as a sign of respect Nursing decoded esteem, care, recognition of human value in themselves and in others, to overcome hatred, conflict, ignorance, by saying of love and justice, as conditions of realization of humanity as a contribution to building the image of the nurse.